Fabrication and characterization of electrospun fatty acid form‐stable phase change materials in the presence of copper nanoparticles. (22nd June 2020) - Xie, Ning; Niu, Junyi; Gao, Xuenong; Fang, Yutang; Zhang, Zhengguo
Summary: Latent heat storage system using phase change materials (PCMs) has been recognized as one of the most useful technologies for energy conservation. In this study, a novel type of fatty acid eutectic of methyl palmitate (MP) and lauric acid (LA)/polyacrylonitrile (PAN) composite phase change fiber is prepared by single electrospinning method. Additionally, copper nanoparticles (CNPs) with different mass ratio are combined for improving the thermal conductivity of the PCM. The structure and morphology of the fabricated composite PCMs are observed by scanning electron microscopy (SEM), and the thermal properties and performance are also characterized. SEM results show that the liquid fatty acid has been fully stabled by the three‐dimensional structure of the fibers. Good compatibility among the components of the composites is also demonstrated. Besides, the addition of nanoparticles leads to an improved thermal conductivity by over 115.2% and a phase transition temperature 21.24 °C as well as a high latent heat of 85.07 J/g. Moreover, excellent thermal reliability of the phase change fiber is confirmed by multiple thermal cycles. Hence, the composite PCM prepared in this study shows a promising potential for thermal energy system such as building insulating and thermal mass regulating textiles. Abstract : Novel methyl palmitate‐lauric acid/polyacrylonitrile/copper nanoparticles phase change fiber is fabricated. Phase change materials are stabilized through electrospinning process. Thermal conductivity is largely enhanced by copper nanoparticles.